TOWARDS MERGING INTERNET OF THINGS (IoT) AND BIG DATA TECHNOLOGIES TO BENEFIT WIDER APPLICATIONS - Alqarni, Hassan; Alqahtani, Abdullah; Alqahtani, Faisal (Acta Scientiae et Intellectus, 2024)
The development of Internet of Things (IoT) makes the life of human being very smooth and easier. IoT provides a tool to control electronic devices in a bit. IoT is actually the network of devices that contain sensors, electronics, softwares, actuators, and connectivity which allows these things to connect, interact and exchange data among each other. IoT made easier to control the devices, collect the information from such devices, manage such information and transfer this information to analyze the same and to predict or prescribe the solution for the problems might exist. Big data image came from the huge quantity of collected data from IoT devices through the sensors. It is not just that there is the only interdependent relation between big data and IoT. As they help each other, in addition to that they hugely impact each other. The fact is, the more the IoT grows it will place more demand on businesses of big data. For example, as the IoT generated data is increasing at a huge rate, conventional data storage technology is already being pushed to its limits. As a result, it demands more advanced and innovative storage solutions to handle these growing workloads resulting in updating the infrastructure of an organization’s big data storage. Similarly, the IoT big data combined applications accelerate the scope of research in both the fields. So, IoT and big data both the technologies carry inter-dependency and need further development.